Heterogenous Cation Exchange Membrane- Fabrication, Characterization And Performance Studies Using Electrochemical Impedance Spectroscopy - Ahmad, Nor Adibah (Universiti Sains Malaysia, 2017)
In this study, novel PVC cation exchange membrane (CEM) and PVC-based mixed matrix membrane were fabricated at different cation exchange resin (CER) and additive concentration, characterized and their performance were tested by using Electrochemical Impedance Spectroscopy (EIS) method. Multi walled carbon nanotubes (MWCNT) was employed as additive in mixed matrix membrane fabrication. CER concentration used in the mixed matrix membranes were determined from the characterization and performance of pure polymeric CER. It was found that water uptake of the CER-CEM was enhanced while the water uptake of MWCNT-CEM was improved with the increasing of nanoparticles but at the highest loading of MWCNT, the water uptake was reduced. Water contact angle was reduced as the CER and MWCNT concentration increases but at high loading of CER and MWCNT, water contact angle was increased. Ion exchange capacity was enhanced as the CER concentration increased, but only up to 8%wt. Membrane with the 8%wt CER loading possessed the highest ion exchange capacity thus it was chosen to be the base of amount of CER in the fabrication of mixed matrix membrane. Ion exchange capacity was reduced as the MWCNT concentration increased due to the high amount of MWCNT that occupied the spaces around CER particles. The ion conductivity was enhanced when the CER loading and MWCNT increased, but suddenly resulting in reduction when CER and MWCNT concentration were at their highest. Ionic conductivity increased from (2.99 to 4.72) Ω−1cm−1 with the addition of MWCNT to the membrane. ElS is an excellent tool to investigate the electrochemical properties of IEM.